Effects of subarachnoid haemorrhage on intracranial prostaglandins. Issue 2 (February 1983) - Walker, V; Pickard, J D; Smythe, P; Eastwood, S; Perry, S
Abstract : Prostaglandins E2, F2 alpha, 6 oxo F1 alpha and thromboxane B2 increased in cisternal CSF following mock subarachnoid haemorrhage in dogs, particularly PGE2 (X25.5). Concentrations were increased also in lumbar CSF of five patients some 8 days after subarachnoid haemorrhage. Subarachnoid haemorrhage did not alter the production of prostaglandins by dog whole cortex or choroid plexuses in vitro, but production by pooled dissected cerebral arteries of PGE2 was increased and of 6 oxo F1 alpha was decreased. Intravenous indomethacin decreased prostaglandin production by cerebral tissues, and caused a marked decrease in the prostacyclin metabolite in CSF. The implications of our findings for the aetiology of cerebral vasospasm are discussed.